2021
DOI: 10.1111/inr.12714
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and health inequalities: Perceptions of social work students and nursing students

Abstract: This study describes student perceptions on health inequalities and causes of poverty. Background: As frontline providers, social workers and nurses are expected to engage with patients from socioeconomically diverse backgrounds. Methods: In this cross-sectional study, a socio-demographic questionnaire, a questionnaire on health inequalities and the Perceived Causes of Poverty Scale were administered using a convenience sample of 155 students in social work and 266 students in nursing undergraduate programmes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Education in social determinants of health, social justice, and sociocultural competence should be an essential element integrated throughout the degree programs. These points are insufficiently taught in nursing programs (Alemany-Arrebola et al, 2021; Demirtas et al, 2021; Habibzadeh et al, 2021). Moreover, no research has been found in which students reflected about how the virus influences those at a higher risk of suffering its wider consequences (specifically in ethnic minorities and socioeconomically vulnerable groups).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education in social determinants of health, social justice, and sociocultural competence should be an essential element integrated throughout the degree programs. These points are insufficiently taught in nursing programs (Alemany-Arrebola et al, 2021; Demirtas et al, 2021; Habibzadeh et al, 2021). Moreover, no research has been found in which students reflected about how the virus influences those at a higher risk of suffering its wider consequences (specifically in ethnic minorities and socioeconomically vulnerable groups).…”
Section: Discussionmentioning
confidence: 99%
“…Future nurses must recognize one’s cultural values, beliefs, and practices about vulnerable populations and eradicate avoidable inequalities related to ethnicity, gender, race, or socioeconomic position, among others (International Council of Nurses, 2021). However, the literature suggests that aspects related to social determinants of health and social justice are insufficiently taught in undergraduate health and social education, specifically in nursing programs (Demirtas et al, 2021; Habibzadeh et al, 2021). This pandemic presents a learning opportunity to promote nursing students’ critical thinking (Riegel et al, 2021) and help them become more aware of the consequences of social inequalities of health (World Health Organization, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, baccalaureate nursing programs have taught advocacy utilizing the lower cognitive processes of knowledge recall and understanding of social health policy and politics; however, the use of higher cognitive processes including application and analysis of policy has not been explored in a meaningful way (Benton et al, 2017;Turale & Kunaviktikul, 2019). A more comprehensive nursing policy and advocacy curriculum which requires higher cognitive processes is warranted to develop leadership competencies that will impact health policy and political activism (Demirtas et al, 2022;Staebler et al, 2017). The Future of Nursing 2020-2030: Charting a Path to Achieve Health Equity (NASEM, 2021) report expands upon the original Future of Nursing's (2011) recommendations regarding nursing's role in advocacy for patients via health policy (IOM (Institute of Medicine), 2011).…”
Section: Meaningful Integration In Prelicensure Educationmentioning
confidence: 99%
“…Nurse educators are nurse leaders to the student body they prepare for nursing practice. As such, nursing faculty can serve as influencers and role models to the student body through competent and active policy engagement, interdisciplinary collaboration, and ongoing continuing education in the policy arena (Demirtas et al, 2022;Ellenbecker et al, 2017;Persaud, 2018). As active advocates, nurse educators can shape student growth in policy advocacy and activism through the creation of partnerships with community stakeholders that provide experiences that intentionally expose students to the upstream drivers of the social determinants of health (Jordan et al, 2021; National League for Nursing, 2019)…”
Section: Meaningful Integration In Prelicensure Educationmentioning
confidence: 99%
See 1 more Smart Citation